Low-dose propofol as a solo agent for sedation in postoperative ventilated liver transplant recipients: A preliminary observational study - Rishabh Jaju; Kelika Prakash; M K Arora (Wolters Kluwer Medknow Publications, 2023)
Background and Aims: Propofol is a commonly used sedative agent, in a dose of 1.5-4.5 mg.kg-1.h-1. Following liver transplantation (LT), drug metabolism may be altered due to liver mass, altered hepatic blood flow, reduced levels of serum proteins, and liver regeneration. Thus, we hypothesized that propofol requirements in this group of patients would be different as compared to the standard dose. This study evaluated the dose of propofol used for sedation in electively ventilated living donor liver transplantation (LDLT) recipients. Material and Methods: After patients were shifted to the postoperative intensive care unit (ICU) following LDLT surgery, propofol infusion was started at a dose of 1 mg.kg-1.h-1 and titrated to maintain a bispectral index (BIS) value of 60-80. No other sedatives such as opioids or benzodiazepines were used. Dose of propofol, noradrenaline, and arterial lactate levels were noted 2 hourly. Results: The mean propofol dose required in these patients was 1.02 ± 0.26 mg.kg-1.h-1. Noradrenaline was gradually tapered off and stopped within 14 h of shifting to ICU. The mean duration between the time of cessation of propofol infusion till extubation was 2.06 ± 1.44 h. Propofol dose did not correlate with respective lactate levels, ammonia levels, or graft-to-recipient weight ratio. Conclusion: The dose range of propofol required for postoperative sedation in LDLT recipients was lower than the conventional dose.